Análise e melhoria de processos: compras e serviços do Ministério Público da Paraíba por dispensa e inexigibilidade de licitação - Silva, Pedro Weiny Alves da (2019)
In a competitive world with limited financial resources, organizations are increasingly concerned with ensuring effectiveness and efficiency in the management processes they hold. Public administration currently evolves in its organizations through the adoption of the managerial model as a counterpoint to the bureaucratic management model, although the latter still has significant evidence in organizations, due to several factors. Knowing the organizational processes in depth and understanding their dynamics is a key factor in the implementation of an adequate and modern organizational culture. In this sense, the mapping and the proposals of improvement to the management processes have relevance in helping to reach these objectives, realizing transformations in the activities of the organizations. This work aims to identify, analyze and suggest possible points for improvement in the procurement process and services for waiver and unenforceability of bidding developed by the Administrative Board and other sectors of the Public Ministry of Paraíba. In order to achieve this objective, the work uses a perspective used by business process management, with theoretical support of ISO-TR 26122: 2008, expressing the design and redesign of the organizational process through the notation Business Process Modeling Notation (BPMN) and using the method of analysis of added value to the process when analyzing its activities.